Psychological science in Argentina: current state & future directions - Giovannetti, Federico (2022)
Psychology was internationally developed as a scientific discipline. However, there continues to be a bias towards thepublication of research with Western English?speaking samples. In consequence, it is important to understand what chal-lenges non-English speaking countries are facing in their ability to contribute their research. Considering this, the goal ofthis article is to present an overview of the factors that may affect the development of scientific psychology in Argentina,including the professional practice of psychology, the teaching of psychology in higher education, and obstacles facedby graduate students who pursue research careers. Reviewing these topics will allow us to present the current state ofpsychological science in Argentina, and to propose future directions for scientific development.